Methacrylic Acid (MAA)-chemical grafted polyethersulfone nanofiltration membrane for forward osmosis application - Siti Nudra Shafinie, Ab Aziz; Mazrul Nizam, Abu Seman; Syed Mohd Saufi, Tuan Chik; Abdul Wahab, Mohammad (John Wiley & Sons, Inc., 2025)
This study successfully modiﬁes NF2 PES membrane via chemical grafting with methacrylic acid (MAA) at predetermined monomer concentrations, reaction times, and initiator concentrations by means of producing forward osmosis (FO) membrane. The membranes are utilized in the FO system, and performance is discussed in terms of water and solute ﬂux. The surface characteristics of the modiﬁed membrane are analyzed in terms of water contact angle, functional groups, and degree of grafting (DG), meanwhile, morphological studies are analyzed via AFM and FESEM characterization. Based on the FO test performance, it can be concluded that increasing monomer concentration results in an increase in the permeate ﬂuxes until a certain value is reached; only then does the permeate ﬂux start to decrease. However, the eﬀect of monomer concentrations is not signiﬁcant on the permeate ﬂux when shorter reactions are applied. This is probably due to the limitation of reaction time, which only allows certain values at a time for co-polymerization to be completed, hence aﬀecting the permeate ﬂux. Increasing reaction time oﬀers more reactions to occur, leading to more surface grafting activity. However, prolonging the reaction time does not always improve the surface grafting, especially when higher monomer concentration and initiator concentration are involved.